Bioaccumulation of lead, cadmium and mercury in Argopecten purpuratus (LAMARCK, 1819) and Aulacomya ater (Molina, 1782), commercial species from Peru, and risk assessment - Barriga-Sánchez, Maritza (2018)
The aim of the study was to determinate the level of lead, cadmium and mercury on the edible part of Peruvian scallop (Argopecten purpuratus Lamarck, 1819) and mussel (Aulacomya ater Molina, 1782) from 2009 to 2012 in the major production areas of Peru and to compare the results with the maximum levels set by the European Union (EU) and consequently evaluate any health risks for consumers. Peruvian scallop samples from suspended culture were extracted from growing areas of Sechura, Samanco and Paracas. Mussel samples were extracted from natural banks from Marcona and Atico. THQ (target hazard quontient) values for Pb, Cd, Hg in Peruvian scallops, plus Pb and Hg in mussels were less than 1 (even less than 0.25), unlike Cd in mussels from Marcona and Atico which exceeded the maximum level allowed and presented THQ values greater than 1, representing a possible health risk. A maximum weekly consumption rate was estimated.